2022
DOI: 10.1038/s12276-022-00801-4
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte invasion of the brain after peripheral trauma in zebrafish (Danio rerio)

Abstract: Despite well-known systemic immune reactions in peripheral trauma, little is known about their roles in posttraumatic neurological disorders, such as anxiety, sickness, and cognitive impairment. Leukocyte invasion of the brain, a common denominator of systemic inflammation, is involved in neurological disorders that occur in peripheral inflammatory diseases, whereas the influences of peripheral leukocytes on the brain after peripheral trauma remain largely unclear. In this study, we found that leukocytes, larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Therefore, we analyzed the relationship between various granulocytes and delirium, and although no significant causal associations were obtained, in previous studies neutrophils were shown to possibly mediate central neuroinflammation due to peripheral inflammation, the latter of which further contributes to the decline in learning and cognition. Raymond et al ( 18 ) showed that following distal (caudal) traumatization of the zebrafish resulting in systemic inflammation, leukocytes can invade the brain and increase macrophage, neutrophil, and lymphocyte recruitment and expression of pro-inflammatory mediators in the whole brain/midbrain and forebrain on the first-day post-trauma, inducing an increase in hyperactivity (agitation) and avoidance behaviors. However, there is a lack of clarity regarding the mechanisms by which neutrophils may be involved in the pathogenesis of delirium, mainly owing to the fact that we currently have considerable difficulty in establishing recognized, standardized, and validated animal models of delirium ( 22 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we analyzed the relationship between various granulocytes and delirium, and although no significant causal associations were obtained, in previous studies neutrophils were shown to possibly mediate central neuroinflammation due to peripheral inflammation, the latter of which further contributes to the decline in learning and cognition. Raymond et al ( 18 ) showed that following distal (caudal) traumatization of the zebrafish resulting in systemic inflammation, leukocytes can invade the brain and increase macrophage, neutrophil, and lymphocyte recruitment and expression of pro-inflammatory mediators in the whole brain/midbrain and forebrain on the first-day post-trauma, inducing an increase in hyperactivity (agitation) and avoidance behaviors. However, there is a lack of clarity regarding the mechanisms by which neutrophils may be involved in the pathogenesis of delirium, mainly owing to the fact that we currently have considerable difficulty in establishing recognized, standardized, and validated animal models of delirium ( 22 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…This process may be associated with the induction of neuroinflammation by circulating immune cells and pro-inflammatory mediators through invasion and entry into the damaged blood–brain barrier (BBB) ( 17 ). Extensively activated astrocytes and microglia promote inflammatory storm processes in the brain, which ultimately lead to synaptic dysfunction, neuronal loss, and impaired connectivity of functional networks in brain regions ( 18–20 ). In patients with neurocognitive impairments, the number and activation status of peripheral blood mononuclear cells (PBMCs) are also often abnormally elevated or decreased, which may be related to the severity and stage of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…This process is known to be correlated with the immune response that occurs and facilitates the entry of several effector cells to act in injury, infection, and cellular stress [ 72 ]. In addition, leukocyte infiltration begins as a deleterious complication of oxidative stress [ 73 ] and has additionally been linked to non-CNS neurological disorders (e.g., anxiety and cognitive impairment) in peripheral inflammatory diseases [ 74 ]. There are several investigations that have found the involvement of proinflammatory cytokines in mediating neurological diseases induced by systemic inflammation [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue and organ injuries associated with non-cranial surgery can cause significant whole blood cell alterations, such as significant upregulation of peripheral blood WBC and monocyte levels and platelet function activation after skin incision, characterized by systemic total CD14 + monocyte upregulation and CD4 + T cell activation ( Hildenborg et al, 2022 ). In a peripheral trauma model constructed by amputation experiments on the distal (caudal) part of the zebrafish, leukocyte (mainly macrophage) invasion of the brain occurs during systemic inflammation, and on the first day after trauma, there is a significant upregulation of corpuscular protein 1A (coro1a) + cell (macrophage, neutrophil, and lymphocyte) recruitment in the whole/midbrain and forebrain, and an increase in the mRNA levels of IL-1β, IL-34, IL-6, IL-8, and IL-10 mRNA expression were observed, and the injured zebrafish showed an increase in hyperactive (agitated) and avoidant behaviors ( Chen et al, 2022 ). This finding supports a possible mechanism whereby peripheral inflammation condition alteration may affect brain function by promoting the infiltration of peripheral immune cells into the central nervous system (CNS).…”
Section: Mechanisms By Which Peripheral Inflammation Promotes Central...mentioning
confidence: 99%